A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

Allometric aboveground biomass equations to quantify carbon content of Southeast Australian saltmarsh vegetation - Jami Butler; Clare Duncan; Paul E. Carnell; Anirban Akhand; Stacey M. Trevathan-Tackett; Peter I. Macreadie (Regional Studies in Marine Science, 2025)

Harvest trends, growth and longevity, and population dynamics reveal traditional assumptions for redhorse (Moxostoma spp.) management in Minnesota are not supported - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Allen H. Andrews; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Double-blind, Randomized, Placebo-controlled Crossover Study Evaluating Reducose® Mulberry Leaf Extract at 3 Levels Shows Significant Effects on Postprandial Blood Glucose and Insulin After Eating a Complex Meal - B. Davis; P. Thondre; J. Tammam; I. Butler; M. Lane; A. Gallagher (Journal of the Academy of Nutrition and Dietetics, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Colony life history of the tropical arboreal ant, Cephalotes goniodontus De Andrade, 1999 - I. A. E. Butler; T. Butterfield; M. Janda; D. M. Gordon (Insectes Sociaux, 2024)
Arboreal ants are ecologically important in tropical forests, but there are few studies using DNA markers to examine their population and colony structure. Colonies of the arboreal turtle ant Cephalotes goniodontus create trail networks through the canopy of the tropical forest, in dense vegetation where it is difficult to determine how long a nest is used and how neighboring colonies partition space. We monitored 53 nest sites for up to six years and, using seven microsatellite markers, genotyped samples of workers collected at or near 41 nests over 1–4 years. We calculated average relatedness within samples collected at a given location, and between samples collected at the same location in successive years, and performed pedigree analysis to predict the number of queens that produced each sample of workers. Fifteen samples were highly related ( r ≥ 0.6) from single colonies, of which 11 were monogynous and the remaining four had two queens; 19 were of intermediate relatedness (0.1 ≤ r < 0.6) with 1–6 queens, and 7 were groups of unrelated workers (r < 0.1) from at least 4 queens. Colonies persisted at the same nest site for 2–6 years. The smallest distance we found separating nests of different colonies was 16.2 m. It appears that different colonies may share foraging trails. Our study demonstrates the feasibility of using a cost-efficient genotyping method to provide information on colony structure and life history of ant species.

Connection for conservation: The impact of counting butterflies on nature connectedness and wellbeing in citizen scientists - C.W. Butler; I. Hamlin; M. Richardson; M. Lowe; R. Fox (Biological Conservation, 2024)

Assessing the transformation products and fate of Oxytetracycline by simulated aerobic degradation tests - Federico M. Ivanic; Matías Butler; Carlos I. Borón; Roberto J. Candal (Chemosphere, 2023)

The effect of shade on sheep grazing pasture during summer conditions - Matthew I. Knight; Nick P. Linden; Kym L. Butler; Maxine Rice; Eric N. Ponnampalam; Ralph Behrendt; Ellen C. Jongman (Journal of Veterinary Behavior, 2023)

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

Otolith allometry informs age and growth of long-lived Quillback Carpiodes cyprinus - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2022)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Development of ULYSSIS, a Tool for the Biosynthesis of Cyclotides and Cyclic Knottins - Thomas N. G. Handley; Torsten Kleffmann; Margi I. Butler (International Journal of Peptide Research and Therapeutics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Trait-based approach reveals how marginal reefs respond to acute and chronic disturbance - B. Sommer; I. R. Butler; J. M. Pandolfi (Coral Reefs, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Engineered biosynthesis of cyclotides - Thomas N. G. Handley; Hyon-Xhi Tan; Malcolm T. Rutledge; Hans Henning Brewitz; Joel D. A. Tyndall; Torsten Kleffmann; Margi I. Butler; Russell T. M. Poulter; Sigurd M. Wilbanks (New Zealand Journal of Botany, 2020)

Last Glacial pollen–climate reconstructions from Northland, New Zealand - R.M. Newnham; B. V. Alloway; K.A. Holt; K. Butler; A.B.H. Rees; J.M. Wilmshurst; G. Dunbar; I. Hajdas (Journal of Quaternary Science, 2017)
Despite wide‐ranging interest in the vegetation and climate of Northland, New Zealand, during the last glacial cycle, the region and timeframe lack quantitative climate reconstructions while land‐based pollen records have tended to be poorly dated and fragmentary. The region is also important for geochronology due to the co‐occurrence of the Rotoehu tephra, a widely dispersed isochron near the current limits of radiocarbon dating, and extensive subfossil wood remains of Agathis australis , with strong dendrochronological and dendroclimatological potential. We present new pollen records and temperature reconstructions from three sites set in coastal dune belts from western mid‐Northland (∼35°S), all containing Rotoehu tephra, that collectively span the last 70 ka. The phases and amplitude of temperature changes broadly align with those reported from elsewhere in New Zealand and with marine isotope climate–stratigraphic records, including maximum temperature depression of 6–8 °C during the last glacial maximum. We argue that these climatic patterns are intimately linked to shifts in the southern westerly wind belt, the northern margins of which extend to the region today. Correspondence between the Northland temperature shifts and atmospheric CO 2 supports the model of ocean–atmosphere CO 2 flux modulated by latitudinal migration of the southern westerlies. Copyright © 2017 John Wiley & Sons, Ltd.

Biogeographic variability in the physiological response of the cold‐water coral L ophelia pertusa to ocean acidification - Samuel E. Georgian; Sam Dupont; Melissa Kurman; Adam Butler; Susanna M. Strömberg; Ann I. Larsson; Erik E. Cordes (Marine Ecology, 2016)
While ocean acidification is a global issue, the severity of ecosystem effects is likely to vary considerably at regional scales. The lack of understanding of how biogeographically separated populations will respond to acidification hampers our ability to predict the future of vital ecosystems. Cold‐water corals are important drivers of biodiversity in ocean basins across the world and are considered one of the most vulnerable ecosystems to ocean acidification. We tested the short‐term physiological response of the cold‐water coral Lophelia pertusa to three pH treatments (pH = 7.9, 7.75 and 7.6) for Gulf of Mexico (USA) and Tisler Reef (Norway) populations, and found that reductions in seawater pH elicited contrasting responses. Gulf of Mexico corals exhibited reductions in net calcification, respiration and prey capture rates with decreasing pH. In contrast, Tisler Reef corals showed only slight reductions in net calcification rates under decreased pH conditions while significantly elevating respiration and capture rates. These differences are likely the result of environmental differences (depth, pH, food supply) between the two regions, invoking the potential for local adaptation or acclimatization to alter their response to global change. However, it is also possible that variations in the methodology used in the experiments contributed to the observed differences. Regardless, these results provide insights into the resilience of L. pertusa to ocean acidification as well as the potential influence of regional differences on the viability of species in future oceans.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Extra-tropical atmospheric response to ENSO in the CMIP5 models - Margaret M. Hurwitz; Natalia Calvo; Chaim I. Garfinkel; Amy H. Butler; Sarah Ineson; Chiara Cagnazzo; Elisa Manzini; Cristina Peña-Ortiz (Climate Dynamics, 2014)

Displacement Forecasting Method in Brittle Crack Surrounding Rock Under Excavation Unloading Incorporating Opening Deformation - X. J. Li; W. M. Yang; L. G. Wang; I. B. Butler (Rock Mechanics and Rock Engineering, 2014)

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Porcine reproductive and respiratory syndrome (PRRS): an immune dysregulatory pandemic - J. E. Butler; K. M. Lager; William Golde; Kay S. Faaberg; Marek Sinkora; Crystal Loving; Y. I. Zhang (Immunologic Research, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

The impacts of flooding on the high-latitude, terrigenoclastic influenced coral reefs of Hervey Bay, Queensland, Australia - I. R. Butler; B. Sommer; M. Zann; J.-x. Zhao; J. M. Pandolfi (Coral Reefs, 2013)

Are the teleconnections of Central Pacific and Eastern Pacific El Niño distinct in boreal wintertime? - C. I. Garfinkel; M. M. Hurwitz; D. W. Waugh; A. H. Butler (Climate Dynamics, 2013)

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Precious metal enrichment in the Platreef, Bushveld Complex, South Africa: evidence from homogenized magmatic sulfide melt inclusions - D. A. Holwell; I. McDonald; I. B. Butler (Contributions to Mineralogy and Petrology, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Leptidea sinapis (Wood White butterfly) egg-laying habitat and adult dispersal studies in Herefordshire - S. A. Clarke; D. G. Green; J. Joy; K. Wollen; I. Butler (Journal of Insect Conservation, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Skeletal muscle telomere length in healthy, experienced, endurance runners - Dale E. Rae; Alban Vignaud; Gillian S. Butler-Browne; Lars-Eric Thornell; Colin Sinclair-Smith; E. Wayne Derman; Mike I. Lambert; Malcolm Collins (European Journal of Applied Physiology, 2010)

Hyperglycemic oxoaldehyde, glyoxal, causes barrier dysfunction, cytoskeletal alterations, and inhibition of angiogenesis in vascular endothelial cells: aminoguanidine protection - Sean M. Sliman; Timothy D. Eubank; Sainath R. Kotha; M. Lakshmi Kuppusamy; Shariq I. Sherwani; Elizabeth Susan O’Connor Butler; Periannan Kuppusamy; Sashwati Roy; Clay B. Marsh; David M. Stern; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2010)

Redox-active antioxidant modulation of lipid signaling in vascular endothelial cells: vitamin C induces activation of phospholipase D through phospholipase A2, lipoxygenase, and cyclooxygenase - Emily Steinhour; Shariq I. Sherwani; Jessica N. Mazerik; Valorie Ciapala; Elizabeth O’Connor Butler; Jason P. Cruff; Ulysses Magalang; Sampath Parthasarathy; Chandan K. Sen; Clay B. Marsh; Periannan Kuppusamy; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2008)

Biogeography of seed‐dispersal syndromes, life‐forms and seed sizes among woody rain‐forest plants in Australia's subtropics - D. W. Butler; R. J. Green; D. Lamb; W. J. F. McDonald; P. I. Forster (Journal of Biogeography, 2007)
Aim To enhance our understanding of the evolutionary interactions between seed‐dispersal syndromes, life‐forms, seed size, and habitat characteristics by studying their association with the regional‐scale distributions of subtropical rain‐forest plants in the context of climatic gradients. Location South‐east Queensland, subtropical eastern Australia (152° E, 26° S). Methods We classified 250 rain‐forest sites into six floristic site‐groups based on their woody plant composition. The resulting classification was strongly associated with variation in rainfall. The distribution of species across the floristic site‐groups was used to assign 568 species to seven habitat classes (one class for ‘widespread’ species, with all other species classified according to the site‐group within which they were most frequent). Species were also classified for three other categorical life‐history factors: three dispersal syndromes based on diaspore morphology (fleshy, wind‐assisted, and unadorned); four life‐forms (trees, shrubs and small trees, tall climbers, and short and shrubby climbers); and four seed‐diameter classes ( Results Across the rain forests of south‐east Queensland, the proportion of species with fleshy diaspores or of large stature increases with rainfall. High‐rainfall sites also have larger average seed sizes, but the difference in average seed size between high‐ and low‐rainfall sites is small compared with variation within sites. Among species, those with fleshy fruit tend to have larger seeds and to favour high‐rainfall sites. Very few small trees produce diaspores adapted for wind‐assisted dispersal. On average, species with unadorned diaspores have smaller seeds than those with fleshy diaspores. However, within sites, species with unadorned and fleshy diaspores have similar average seed sizes, and some species with unadorned diaspores from high‐rainfall habitats have extremely large seeds. Main conclusions Commonly observed associations between fleshy fruit, larger plants, larger seeds, and productive habitats are apparent within the rain‐forest flora of south‐east Queensland. However, these associations are generally weak and involve complex interactions. For example, the strong tendency for species with fleshy fruit to have larger seeds than those with unadorned diaspores concealed a significant group of species from wetter forests that produce extremely large seeds and unadorned diaspores. The most widespread species in this study tend to be large plants (particularly robust lianes) and to produce fleshy fruit, but they tend not to have relatively large seeds. The association between large seeds, large plants, fleshy fruit and productive habitats is discussed as part of an evolutionary strategy favouring fitness in populations close to carrying capacity. We review some problems with focusing on establishment chances per seed as the driver towards association between large seeds, large plants and productive rain‐forest habitats (the difficult‐establishment hypothesis). Instead we suggest that production of large, short‐lived seeds by long‐lived plants in temporally stable, closed habitats may reflect the limited evolutionary potential for strategies enhancing colonization (e.g. producing large numbers of dormant seeds), thus allowing the establishment benefits of large seeds greater selective influence (the slow‐replacement hypothesis). The association of fleshy fruit with large seeds probably reflects the difficulty of dispersing large seeds by other means (the difficult‐dispersal hypothesis).

Analyses of a multi-parent population derived from two diverse alfalfa germplasms: testcross evaluations and phenotype–DNA associations - I. J. Maureira-Butler; J. A. Udall; T. C. Osborn (Theoretical and Applied Genetics, 2007)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Neuronal activity in the monkey ventrolateral thalamus following perturbations of voluntary wrist movements - E. G. Butler; Michael C. Harvey; David I. Finkelstein; Malcolm K. Horne (Experimental Brain Research, 1998)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)